(untitled) (Journal of Engineering, 2025)
The physical and social structure of urban residential areas is affected by public open spaces in positive and negative ways. Public spaces serve as the basis for the growth of urban life that promotes physical activities and social relations. The research addressed the problem of lack of knowledge about the mechanisms that contribute to achieving healthy and lively public places according to spatial characteristics. It aimed to develop and improve public places through a more comprehensive knowledge of the effective spatial characteristics that contribute to enhancing the value of public places. The research assumed the existence of a correlation between vital spatial characteristics and healthy environments. For the purpose of testing the hypothesis, the theoretical framework extracted was applied to models of public places in international countries, Such as Canada, Japan, Algeria. The research adopted a qualitative descriptive approach to verify the hypothesis. The results showed that there is a relationship between health and vital environments that helped provide dynamism to the functioning of urban space and can be used as a criterion for measuring the effectiveness of public places.